1993
DOI: 10.1103/physreva.47.3923
|View full text |Cite
|
Sign up to set email alerts
|

Angular distribution of dissociated deuterons by impact of 2–16-MeVO8+

Abstract: The angular distributions of dissociated deuterons for electron capture and ionization by bare oxygen ions with energies from 2 to 16 MeV in collision with molecular deuterium targets were measured. The dependence of the differential cross sections on the alignment of the molecular axis with respect to the beam axis was determined. The results show that in the transfer ionization and transfer excitation processes, the deuterium molecules are more likely to be aligned perpendicular to the incident beam than par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
30
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 23 publications
2
30
0
Order By: Relevance
“…The above theoretical work and subsequent experimental work, however, showed that other global observables show traces of this interference [9][10][11][12][13].…”
mentioning
confidence: 99%
“…The above theoretical work and subsequent experimental work, however, showed that other global observables show traces of this interference [9][10][11][12][13].…”
mentioning
confidence: 99%
“…Only recently, the predictions of Tuan and Gerjuoy were confirmed by several experiments. Variations of the capture cross sections as a function of the molecular orientation could be attributed to interference effects [2][3][4][5]. Later, Schmidt et al [6] observed very pronounced matter wave interference fringes in multiple differential momentum spectra of recoil ions produced in dissociative capture in H þ 2 þ He collisions.…”
mentioning
confidence: 99%
“…Following Deb et al [21], Wang et al [19], and Shingal and Lin [22] derived equivalent theoretical cross section variations with the H 2 target orientation. Their predictions were recently confirmed for 0.3-1.3 MeV H þ þ H 2 collisions [23], while no direct observation of interference in the outgoing projectile wave was possible in [23] or in the only similar work [24].…”
mentioning
confidence: 99%